Sex education's community problem. Issue 5 (26th October 2022) - Howlett, Caitlin
Abstract: Legislating comprehensive sex education curricula has long been believed to be essential to aligning education about sex, sexuality and human relationships with the values of equality, inclusivity and autonomy. Defences of the need for 'good' sex education in public schools are contingent upon arguments about whose experiences ought to guide us in determining what sufficient alignment with such values might look like. The aim of this paper is to explore the assumptions underlying one prevailing norm in such defences: what I call parental deference or the practice of heeding to the rights of parents in debates about sex education. The question at the heart of this paper is, then, who in our communities does this deference exclude? I begin with a brief consideration of the appeal of parental deference within theories of education in general, and sex education in particular, before problematising its normalisation through a consideration of the exclusions such deference creates. In the process, I aim to explore the limits of parental deference for addressing the intersection of sexuality, sex, gender and race with violence in curricula and argue instead that one way of mitigating the consequences of these limits is to take seriously what I call sex education's community problem: If schools are to serve communities, why are so many community members' experiences excluded?